Effects of polymer blend composition on membrane properties and separation performance of PEES/PEI blend membrane. (May 2017) - Saranya, R; Beril, JS; Mohan, D
In this work, an attempt has been made for protein rejection from aqueous solution using ultrafiltration blend membrane based on poly(phenylene ether ether sulfone) (PEES) and polyetherimide (PEI) was prepared in various blend compositions. Prepared membranes were characterized in terms of pure water flux, water content, membrane hydraulic resistance, porosity, contact angle, scanning electron microscopy, thermogravimetric analysis, and attenuated total reflectance-Fourier transform infrared spectroscopy. Studies were carried out to find out the rejection of proteins such as trypsin, pepsin, egg albumin, and bovine serum albumin. The extent of protein separation is directly proportional to molecular weight of protein. Pristine PEES membrane exhibited high-percentage protein rejection of BSA (92.7%), EA (88.2%), pepsin (85.8%), and trypsin (82.2%) compared to PEES/PEI blend membranes. PEES/PEI blend membranes have better hydrophilic property compared to pristine PEES membrane. Pristine PEES has a contact angle of 97.8°, embedded with PEI and reduced to 67.9°. The thermal stability of the membrane was slightly decreased when the percentage of PEI composition into the PEES/PEI blend increased and observed that the pure PEES membrane has superior thermal stability than PEES/PEI blend membranes